Interpolation by Loop's Subdivision Functions (Journal of Computational Mathematics, 2005)
For the problem of constructing smooth functions over arbitrary surfaces from discrete data, we propose to use Loop's subdivision functions as the interpolants. Results on the existence, uniqueness and error bound of the interpolants are established. An efficient progressive computation algorithm for the interpolants is also presented.
Keywords: Interpolation; Loop's subdivision function.